2020
DOI: 10.1167/iovs.61.11.20
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chromosome X in Intraocular Pressure Variation and Sex-Specific Effects

Abstract: Purpose The purpose of this study was to identify genetic variants on chromosome X associated with intraocular pressure (IOP) and determine if they possess any sex-specific effects. Methods Association analyses were performed across chromosome X using 102,407 participants from the UK Biobank. Replication and validation analyses were conducted in an additional 6599 participants from the EPIC-Norfolk cohort, and an independent 331,682 participants from the UK Biobank. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Although the association between CH and glaucoma has been less thoroughly examined in previous literature, multiple studies have demonstrated that CH is strongly associated with glaucoma presence, risk of progression, and effectiveness of certain treatments. [35][36][37][38][39][40][41] Even in patients with glaucoma and well-controlled intraocular pressure, lower CH was associated with a higher risk of global visual field progression. 42 Low CH has also been found to be a risk factor for central visual field progression, which is a major concern for vision-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between CH and glaucoma has been less thoroughly examined in previous literature, multiple studies have demonstrated that CH is strongly associated with glaucoma presence, risk of progression, and effectiveness of certain treatments. [35][36][37][38][39][40][41] Even in patients with glaucoma and well-controlled intraocular pressure, lower CH was associated with a higher risk of global visual field progression. 42 Low CH has also been found to be a risk factor for central visual field progression, which is a major concern for vision-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Simcoe et al. 2020). For example, in humans and rats, the gene GPM6B may escape X‐inactivation and result in higher intraocular pressure, which could lead to glaucoma (Mirzaei et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Simcoe et al. 2020). Additional studies are improving our understanding of differential sex bias expression in mammals (Bwire, 2020; Ytrehus et al.…”
Section: Discussionmentioning
confidence: 99%
“…First, sex could be a potential factor conditioning intraocular pressure due to sex hormones and genetic variants [ 49 , 50 , 51 ]. However, the findings encountered in the scientific literature are not consistent.…”
Section: Discussionmentioning
confidence: 99%